Moderation in Islamic Da'wah and Christian Mission - Jamallius, Rido; Yusna, Darni; Ashadi, Andri (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This research aims to comprehend the concept of moderation in Islamic preaching and Christian missions. The research has three objectives: firstly, to uncover the practice of moderation in Islamic preaching; secondly, to elucidate the manifestation of moderation in Christian missions; and thirdly, to analyze the similarities and differences between moderation in Islamic preaching and Christian missions. Employing a qualitative text-based research method with a literature review approach, the study is conducted on social media platforms by searching for articles from relevant journals. The data sources consist of secondary data collected from literature obtained from journals related to the research problem. Data collection involves searching for journals browsed on portals such as Garuda, Moraref, DOAJ, Google Scholar, and the National Library. Data analysis encompasses data reduction, data classification, data presentation, and data interpretation. The results reveal that the concept of moderation in Islamic preaching facilitates the peaceful and tolerant delivery of preaching invitations with openness to all religious differences. Essentially, moderation in Christian missions aims to prevent extreme, radical, and excessive attitudes in practicing Christian teachings. Additionally, it embraces all religious diversity within Christianity. This research concludes that moderation in Islamic preaching promotes balanced preaching delivery, fostering mutual respect among Muslims. Meanwhile, moderation in Christian missions requires an open-minded approach that embraces all religious differences within Christianity.